2018
DOI: 10.1590/s0100-83582017350100084
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Ether Sulfate Improves Efficacy of Herbicides Against Common Goosefoot and Field Bindweed in Wheat

Abstract: -Tank mixed application of herbicides with adjuvant is required for effective weed management and to reduce herbicide load on agricultural crops. Field studies were conducted to investigate the effect of herbicides at reduced rates with adjuvant on common goosefoot (Chenopodium album) and field bindweed (Convolvulus arvensis) and grain yield of wheat for two consecutive winter seasons. Treatments included post-emergence foliar application of four herbicides viz., fluroxypyr + tribenuron-methyl + clopyralid, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Further, the combined application of herbicide with adjuvants increases herbicide efficiency and retention and decreases surface tension through cuticle layer absorption (Zhang et al, 2013). Our findings of the study also line with Tanveer, Abbas, Safdar, & Ikram (2017) who concluded that 75% (MCPA + bromoxyinal + iodosulfuron-methyl sodium) with adjuvant ammonium sulfate reduced weeds density up to 25% and dry weight up to 56% of broadleaf weeds. Moreover, our data showed similarity with Donald (1985) who reported that herbicide chlorsulfuron with surfactant (0.2% v/v Tween 80) as adjuvant reduced dry mass of weeds up to 67.4% and also stop further growth of weeds.…”
Section: The Effect Of Herbicides On Weed Growth With and Without Adjuvantssupporting
confidence: 88%
See 2 more Smart Citations
“…Further, the combined application of herbicide with adjuvants increases herbicide efficiency and retention and decreases surface tension through cuticle layer absorption (Zhang et al, 2013). Our findings of the study also line with Tanveer, Abbas, Safdar, & Ikram (2017) who concluded that 75% (MCPA + bromoxyinal + iodosulfuron-methyl sodium) with adjuvant ammonium sulfate reduced weeds density up to 25% and dry weight up to 56% of broadleaf weeds. Moreover, our data showed similarity with Donald (1985) who reported that herbicide chlorsulfuron with surfactant (0.2% v/v Tween 80) as adjuvant reduced dry mass of weeds up to 67.4% and also stop further growth of weeds.…”
Section: The Effect Of Herbicides On Weed Growth With and Without Adjuvantssupporting
confidence: 88%
“…Maximum BY, PY and HI were recorded with 75% N + AS that were statistically (P ≤ 0.05) similar with all other weeds control treatments except weedy check and 75% reduced dose of Kelion and Ryzelan. These results are close to Tanveer, Abbas, Safdar, & Ikram (2017) who concluded a 75% reduced dose of herbicides (MCPA + bromoxynil + iodosulfuronmethyl sodium) with adjuvants (alkyl ether sulfate) gave the significant results with 10.46-56.1% increase in yield of wheat over control. These results were similar to Hammami, Aliverdi, & Parsa (2014) who concluded that the application of propanil with surfactant and methylated seed oil as adjuvant gave significant results to control barnyard grass and higher yield of rice.…”
Section: The Effect Of Herbicides On Rice Yield Components With and Without Adjuvantssupporting
confidence: 87%
See 1 more Smart Citation
“…Important impact of adjuvant has been the recover attributes of herbicide mixture, impact on sublimation, upgrade of maintenance, alteration or improvement of spray pledges and additionally an enhanced entrance and relocation. Alkyl ether sulfate (AES) has been ended up being a decent adjuvant as it can help in reducing herbicide dose up to 75% of prescribed dose without impairing its adequacy and brought about higher grain yield (Tanveer et al, 2017). Singh et al (2004) brought about an investigation to monitor the adequacy of glyphosate only and in mixture with additives (MON 0818) to minimize the density of parthenium.…”
Section: Application Of Adjuvantmentioning
confidence: 99%
“…Copyright © 2021 Universitas Sebelas Maret sodium along with AES adjuvant were more effective against weeds along with the higher grain yields of wheat (Tanveer et al, 2017).…”
Section: Application Of Adjuvantmentioning
confidence: 99%